Direct induction of adventitious root in Schefflera octophylla (Lour.) Harms from leaf explants cultured in vitro - Thi Luy, Huynh; Huu Ho, Nguyen; Van Le, Bui (Vietnam Journal of Biotechnology, 2021)
Schefflera octophylla (Lour.) Harms is a precious plant species belonging to the Araliaceae family. All parts of plant have been used to create products for human health. In tissue culture of medicinal plants, the induction and multiplication of adventitious root of Schefflera octophylla for biomass collection have been studied. In this report, results on induction of adventitious root from leaf explants cultured in vitro of this plant species were presented. Leaf disks ( 10 x 10 mm), leaf transverse - thin cell layers (t-TCLs) ( 3 x 10 mm) were cultured on different mineral media MS, ½MS, B5, SH with NAA (0 - 5 mg/L), sucrose (0 - 50 g/L) and light intensity (0 - 4,000 lux). The results showed that, 30 days after culturing on ½MS solid medium plus 3 mg/L NAA, and 30 g/L sucrose in 4,000 lux light condition, direct formation of adventitious root was best from leaf disks, t-TCLs with rooting rate (%) 100, 100; root number/sample 68.80, 21.96; root lenght (mm) 16.53, 15.53, respectively. Leaf disk culture resulted in better rooting than t-TCL culture in two criteria of root number and root length. Morphological and histological observations of adventitious root primordia formation in the leaf disk were also performed. This is the first report on direct formation of adventitious root by in vitro culture of leaf disks/t-TCLs in Schefflera octophylla with very high efficiency, creating basis for further studies on root biomass multiplication for production of bioactive compounds.